2014
DOI: 10.1186/1556-276x-9-444
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterizations of Ni-NiO nanoparticles on PDDA-modified graphene for oxygen reduction reaction

Abstract: We are presenting our recent research results about the Ni-NiO nanoparticles on poly-(diallyldimethylammonium chloride)-modified graphene sheet (Ni-NiO/PDDA-G) nanocomposites prepared by the hydrothermal method at 90°C for 24 h. The Ni-NiO nanoparticles on PDDA-modified graphene sheets are measured by transmission electron microscopy (TEM), energy-dispersive X-ray spectroscopy (EDS), and selected area electron diffraction (SAED) pattern for exploring the structural evidence to apply in the electrochemical cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…For the production of hydrogen, these materials display excellent catalytic behavior during electrocatalytic water splitting for the hydrogen evolution reaction (HER) (Gong et al 2014). Here, Pt is regarded as state-of-the-art material and is often used as a benchmark (Cheng et al 2016;Subbaraman et al 2011;Yin et al 2015); but because of its dearth in nature, other materials are needed (Yung et al 2014). One alternative is Ni/NiO, where theoretical studies have identified active sites on Ni(111) near the interface of NiO that provides HER performance that can be equal or even higher than that of Pt (Pan and Zhou 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For the production of hydrogen, these materials display excellent catalytic behavior during electrocatalytic water splitting for the hydrogen evolution reaction (HER) (Gong et al 2014). Here, Pt is regarded as state-of-the-art material and is often used as a benchmark (Cheng et al 2016;Subbaraman et al 2011;Yin et al 2015); but because of its dearth in nature, other materials are needed (Yung et al 2014). One alternative is Ni/NiO, where theoretical studies have identified active sites on Ni(111) near the interface of NiO that provides HER performance that can be equal or even higher than that of Pt (Pan and Zhou 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The peak at 25.4°, corresponding to the characteristic crystal diffraction of the graphene structure (002) was observed in the XRD spectrum of rGO paper. In XRD data of NiMOF, the peaks at about 35.6°, 42.1°, 45.3°, 50.2°, 62.2°, and 75.4 correspond to the (111), (200), (220), (311), and (222) structure of Ni, respectively (JCPDS card No: 47–1049) . In the XRD pattern of NiMOF/rGO paper, diffraction peaks of both rGO and NiMOF powder structure were observed which indicates the successful preparation of NiMOF/rGO composite paper.…”
Section: Resultsmentioning
confidence: 96%
“…The broadened 2θ peak of graphene (002) plane is found at approximately 23°-25°. However, the graphene (002) plane of PtNi/PDDA-G nanohybrids shifted to 20.5°-21°, which shows that the interplanar spacing (d spacing) of graphene is expanded by the intercalation of PDDA, as shown in Figure 1b [21][22][23][24]. Furthermore, three XRD peaks is observed at 2θ = 40.2°, 46.3°, and 67.6°, which attributed to the crystalline plane of (111), (200) and (220) planes in the PtNi alloy nanoparticles, respectively [25,26].…”
Section: Resultsmentioning
confidence: 96%